THE STUDENTS’ LEARNING OUTCOME OF SCIENCE PHYSICS PROCESS SKILL THROUGH IMPLEMENTING SCIENTIFIC APPROACH AT SMPN 1 RAMBAH SAMO - Atik Rahmawati Atik Rahmawati; Muhamad Nasir Muhamad Nasir; Muhamad Sahal Muhamad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aimed to describe  the students’ learning outcome of science physic process skill through implementing scientific approach in heat lesson in class VII1 SMPN 1 Rambah Samo. The subjects of this research were the students in class VII1. They were 29 students that consisted of 15 male and 14 female students. The instrument of collecting data used was the test of the students’ process skill learning outcomes. The data analysis used was descriptive analysis to portray the description of students’ process skill learning outcomes by using the criteria of absorption, the effectiveness of learning, and the completeness of students’ learning. From the analyzed data, it showed that: the average of class absorption was 78,97% with a good category, the effectiveness of learning declared in effective way, the completeness of students’ learning classically worth 72, 41% and it was categorized as incomplete, and the completeness of lesson worth 100% and declared as complete. Therefore, the learning outcome of science physicsprocess skill through scientific approach was effective for the learning process in class VII1 SMPN 1 Rambah Samo.   KeyWords  : learning outcome,process skill,scientific approach